Answer:it’s actually -60x + 32 = -60x + 60
And
-60x +32 = -60x-32
Step-by-step explanation:
Answer:
-60.X + 32 = 32.r – 60
Because we only have one equation for 2 unknowns.
All the equations have solution for r but the one that has 2 unknowns (r and X).
That is because we only have one equation and 2 unknowns.
Then, we only can express one unknown in function of the other and have an indeterminate solution.
the answer for that is :
x = 7
m=9
11-9m=-70
-11 -11
-9m = -81
divide both sides by -9 and you get m=9